1977
DOI: 10.1128/jb.130.3.1310-1316.1977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hypocholesteremic agent trifluperidol on the sterol, steryl ester, and fatty acid metabolism of Saccharomyces cerevisiae

Abstract: Trifluperidol (TFP), at a concentration of 100 ,M, inhibited the 24-h growth of Saccharomyces cerevisiae by about 30%. Effects on lipid metabolism were investigated by monitoring the incorporation of [1-14C]sodium acetate into various lipid fractions after 4 and 24 h of growth in the presence of several concentrations of TFP. Although little effect was noted on the amount of free sterols, 24-h incorporation of label into steryl esters was increased two-to fourfold by 100 ,M TFP. Major sterol components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The haloperidol analogue trifluperidol is clinically used as an antipsychotic. Besides its prominent antidopaminergic activity trifluperidol also inhibits the yeast sterol C 8 –C 7 isomerase (Sobus et al , 1977). It differs from haloperidol by a trifluoromethyl group instead of a chlorine atom and has modestly lower affinity ( K i 0.83 ± 0.24 n m ( n = 3)) than haloperidol ( K i 0.2 n m (Hanner et al , 1996)) for the liver (+)‐[ 3 H]‐pentazocine binding site (Table 1, Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The haloperidol analogue trifluperidol is clinically used as an antipsychotic. Besides its prominent antidopaminergic activity trifluperidol also inhibits the yeast sterol C 8 –C 7 isomerase (Sobus et al , 1977). It differs from haloperidol by a trifluoromethyl group instead of a chlorine atom and has modestly lower affinity ( K i 0.83 ± 0.24 n m ( n = 3)) than haloperidol ( K i 0.2 n m (Hanner et al , 1996)) for the liver (+)‐[ 3 H]‐pentazocine binding site (Table 1, Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The ultrahigh affinity of fenpropimorph for the brain α 1 ‐site ( K i 5 p m ) suggests that this morpholine might be a valuable tool for studies on sigma 1 ‐mediated effects. The haloperidol congener trifluperidol ( K i 1.3 n m ) inhibits the sterol C 8 –C 7 isomerase of yeast (Sobus et al , 1977) whereas the azadecalin MDL28,815 ( K i 0.16 n m ) inhibits the mammalian sterol C 8 –C 7 isomerase in 3T3 mouse fibroblasts (Gerst et al , 1988) as well as in the human hepatoma cell line HepG2 (van Sickle et al , 1993). The anti‐hypercholesteraemic drug AY‐9944 ( K i 0.46 n m ) reduces sterol C 8 –C 7 isomerization in yeast (Pereira et al , 1983) and rat adrenal gland (Givner et al , 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Although hydrolase enzyme is observed, the low activity would fail to account for the pool of free sterols present in the cells during the early growth phases. Yeast cultured under growth inhibitory conditions caused by trifluperidol also accumulate sterol esters (14). Thus, esterification cannot be caused simply by exhaustion of growth nutrients from the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of DMAE-DHA concentration on the extent of total sterol esterification is also of interest. Earlier work indicated that exposure of yeast to either trifluperidol (20) or triparanol (21) resulted in the production of at least twice as much esterified sterol as in control cultures. The increased sterol esterification occurring in the presence of these drugs may be due to the accumulation of A8 sterols, since they appear to be better substrates than ergosterol for esterification (22).…”
Section: Discussionmentioning
confidence: 99%